2019
DOI: 10.1155/2019/4602371
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Clinical Significance and Prognostic Value of the lncRNA ACVR2B-As1 in Liver Cancer

Abstract: A refined liver cancer staging system and effective prognostic prediction can help clinicians make optimized treatment decisions, which is essential in our fight against cancer and for improving the unsatisfying survival rate of liver cancer globally. The prognosis of liver cancer is not only related to tumor status, it is also affected by the patients' liver functions and the chosen treatment. Currently, several staging systems are being tested. Herein, we analyzed RNA-seq data from the TCGA database and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Finding promising biomarkers can accurately assess the prognosis and timely assist systemic treatment of liver cancer patients. Many researches have been seeking the diagnostic and prognostic biomarkers all the time [26][27][28][29][30][31][32][33][34][35][36][37]. Here, we first found that HN1 mRNA overexpressed in liver cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Finding promising biomarkers can accurately assess the prognosis and timely assist systemic treatment of liver cancer patients. Many researches have been seeking the diagnostic and prognostic biomarkers all the time [26][27][28][29][30][31][32][33][34][35][36][37]. Here, we first found that HN1 mRNA overexpressed in liver cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Our group has, after a long period of research, identified a variety of novel LC biomarkers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. This study confirmed that hepatic PDK2 levels were lower in cancerous tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 54%
“…In recent years, bioinformatics has attracted much attention because of its significance in screening markers. We also have been working on the exploration biomarkers for different types of cancer by bioinformatics [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%